Utilization of MS 222 in Transport of Catfish (Pangasius sutchi) Seed - Arfah, Harton; Supriyono, Eddy (Indonesian Society of Scientific Aquaculture (ISSA), 2002)
ABSTRACTProblems faced in supplying seed out of Java especially Bogor to Sumatera, for instance, are it only contains few seed (100 seeds/l) and it has a high mortality rate because of stress during transport. This experiment was conducted to know the effect of MS 222 in keeping fish metabolism activity down while taking note of its survival rate and change of water quality. The experimental design used here was factorial design 3x5 with 3 repetitions. Dosages of MS–222 were 0, 25 and 50 ppm and the fish densities were 100, 300, 400, 500 and 600 per liter. As container was plastic bag (volume 10 l). After putting the fish into the plastic bag, it was filled up with oxygen, which the volume was 3 times than water volume, than the plastic bag was closed by tying it. After 18 hours of treatment the survival rate and water quality were checked. Based on evaluation of survival rate, it was concluded that the combination between 25 ppm of MS 222 and fish density, which was 500 per liter, gave an optimum result.Keywords: Catfish, Pangasius sutchi, live transport, stress, MS–222, survival rate ABSTRAKKendala yang dihadapi dalam pemasokan benih ikan patin dari pulau Jawa terutama Bogor, keluar pulau Jawa terutama Sumatera adalah jumlah ikan yang terangkut masih sedikit (± 100 ekor/l) dan tingkat kematian yang cukup tinggi, karena stres selama perjalanan. Penelitian ini dilakukan untuk mengetahui pengaruh penggunaan MS–222 dalam menekan aktivitas metabolisme ikan dengan memperhatikan tingkat kelangsungan ikan dan perubahan kualitas air. Penelitian ini menggunakan rancangan faktorial 3x5 dengan 3 ulangan. Dosis MS–222 yang digunakan: 0,25 dan 50 ppm dan kepadatan ikan: 100, 300, 400, 500 dan 600 ekor/l. Wadah pengangkutan berupa kantong plastik (volume 10 l). Ikan yang diangkut dimasukkan ke dalam kantong plastik, kemudian dipompakan oksigen sebanyak 3 kali volume air, selanjutnya dilakukan pengikatan. Setelah 18 jam perlakuan dilakukan perhitungan terhadap tingkat kelangsungan hidup ikan dan perubahan kualitas air media. Hasil penelitian ini menunjukkan kombinasi penggunaan MS–222 25 ppm dan kepadatan ikan 500 ekor/l memberikan tingkat kelangsungan hidup yang optimal.Kata kunci: Ikan patin, Pangasius sutchi, pengangkutan hidup, stres, MS–222, tingkat kelangsungan hidup.